2006
DOI: 10.1677/joe.1.06642
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous glucocorticoids cause thymus atrophy but are protective during acute Trypanosoma cruzi infection

Abstract: The cytokine-mediated stimulation of the hypothalamuspituitary-adrenal (HPA) axis is relevant for survival during bacterial endotoxemia and certain viral infections. However, only limited information is available regarding the effects of endogenous glucocorticoids on parasite diseases. We have studied this issue using, as a model, C57Bl/6 and Balb/c mice infected with Trypanosoma cruzi, the causal agent of Chagas' disease. These two mouse strains differ in the susceptibility to infection with the parasite. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
122
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 39 publications
(41 reference statements)
8
122
1
5
Order By: Relevance
“…These results are in agreement with observations in T. cruzi-infected mice that TNF-α is critical for protection during acute Chagas disease, but could also be deleterious when excessively produced, which would induce vulnerability and death (Roggero et al 2002(Roggero et al , 2004(Roggero et al , 2009. In addition, similar to studies in mice (Roggero et al 2006, Pérez et al 2007), TNF-α production in our infected young rats preceded HPA axis activation and resulted in increased CT levels. The CT response observed in young rats may represent an aggravation in view of the functional alterations that glucocorticoids exert on immune cell populations (Sapolsky et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with observations in T. cruzi-infected mice that TNF-α is critical for protection during acute Chagas disease, but could also be deleterious when excessively produced, which would induce vulnerability and death (Roggero et al 2002(Roggero et al , 2004(Roggero et al , 2009. In addition, similar to studies in mice (Roggero et al 2006, Pérez et al 2007), TNF-α production in our infected young rats preceded HPA axis activation and resulted in increased CT levels. The CT response observed in young rats may represent an aggravation in view of the functional alterations that glucocorticoids exert on immune cell populations (Sapolsky et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Recent experimental evidence from studies in adult mice and rats showed that there was an endocrine response associated with the immune process that strongly affected the course of T. cruzi infection and appeared to be influenced by basal levels of glucocorticoids, the kinetics of corticosterone (CT) release and gonadal axis manipulations (Corrêa-de-Santana et al 2006, Roggero et al 2006, do Prado et al 1999.…”
mentioning
confidence: 99%
“…In addition to the mechanisms discussed in this review, other aspects of the immune system including various endocrine factors and regulatory T cell subtypes may be influential or even subverted during T. cruzi infection, leading to pathological consequences. For example, several studies have linked differential expression of corticosterioids with variations in susceptibility of different mouse strains to T. cruzi infection [68,69]. Although initial reports suggest traditional CD4+CD25+ regulatory T cells do not play a significant role in regulating acute phase responses to T. cruzi infection in mice, investigation into the role of regulatory T cells during T. cruzi infection has not been exhaustive [70].…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of glucocorticoid receptors (using RU486) during acute infection can partially reverse this atrophy (Roggero et al, 2006). Thymic atrophy has also been reported in response to graft-versus-host disease, a condition associated with elevated glucocorticoid levels and accelerated apoptosis of immature thymocytes.…”
mentioning
confidence: 99%
“…asthma, Van der Velden, 1998;rheumatoid arthritis, Gaffo et al, 2006), though recent research indicates they may have acute pro-inflammatory qualities as well, especially in response to injury (Sorrells and Sapolsky, 2007). Exogenous glucocorticoid administration decreases pro-inflammatory cytokine release, including TNF-α (Barnes, 1998), and glucocorticoid receptor blockade increases TNF-α levels (Roggero et al, 2006). Thus, we hypothesized that high-locomotion, high-glucocorticoid females would have attenuated TNF-α levels at baseline and/or in responses to tail nicking, compared to lowlocomotion, low-glucocorticoid females.…”
mentioning
confidence: 99%